2021
DOI: 10.1016/j.heliyon.2021.e06126
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high CO2 and low O2 on biochemical changes in cut Dendrobium orchids

Abstract: Exportation of cut flowers entails long distance transportation, and the quality of cut flowers deteriorates as the distance and transportation time increase. Low storage temperatures and modified atmosphere are commonly used to extend the life of cut flowers. As a result, this research explored the potential use of high CO 2 and low O 2 to prolong the shelf life of cut flowers. Specifically, this study examined the effects of high CO 2 and low O 2 storage on the biochemical changes in cut Dendrobium pink stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…Specifically, CO 2 competed for the receptor sites with ethylene ( Poonsri, 2020 ). In addition, the semi-permeability of plastic films altered the internal atmosphere (higher CO 2 and lower O 2 ), which reduced the ethylene production and ethylene action ( Brandes and Zude-Sasse, 2019 ; Kader, 2002 ; Andrew et al., 2009 ; Poonsri, 2021 ). Specifically, the ethylene production was reduced as low O 2 inhibited the conversion of 1-aminocyclopropane-1-carboxylic acid (ACC) into ethylene ( Poonsri, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, CO 2 competed for the receptor sites with ethylene ( Poonsri, 2020 ). In addition, the semi-permeability of plastic films altered the internal atmosphere (higher CO 2 and lower O 2 ), which reduced the ethylene production and ethylene action ( Brandes and Zude-Sasse, 2019 ; Kader, 2002 ; Andrew et al., 2009 ; Poonsri, 2021 ). Specifically, the ethylene production was reduced as low O 2 inhibited the conversion of 1-aminocyclopropane-1-carboxylic acid (ACC) into ethylene ( Poonsri, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…In comparison with air-stored flowers, those retained in PP-film passive MAP had lower water vapor transmission and longer shelf life ( Singh et al., 2009 ). In addition, the orchid flowers wrapped in PP-film passive MAP had higher internal CO 2 , lower respiration rate, and lower ethylene production, vis-à-vis those stored in PP-film active MAP ( Uthairatanakij et al., 2010 ; Poonsri, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The extended vase life under conditions of 20% CO2 and 10% O2 could be related to reduced respiration rates, ethylene production, and oxidation of the narcissus cut flower under high CO2 and low O2 conditions (authors). The researchers attributed the reduced respiration rate in CO2-treated Dendrobium cut flowers (Ketsa 1986;Poonsri 2021b) to the inhibitory effect of CO2 on phosphofructokinase in the glycolytic pathway. Some studies have reported a positive relationship between water uptake and vase life.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental results depicted in Figure 2 show that an appropriate increase in CO 2 concentration inhibits respiration rate because CO 2 is a product of respiration and can interfere with the Krebs cycle enzymes at high concentrations, leading to decreased fruit metabolism (Martins et al, 2014). However, excess CO 2 induces anaerobic respiration (Poonsri, 2021;Junior et al, 2019), increasing the proportion of CO 2 release from fruits and vegetables. Moreover, because the energy conversion efficiency of anaerobic respiration is low, and large quantities of harmful substances are produced, this inevitably results in dry matter loss and increased cell inactivation, a decrease in water storage capacity, and an increase in the final weight loss rate.…”
Section: Verification Of Storage Testmentioning
confidence: 99%